Violence in the Name of Faith: How Geopolitical Risk Fuels Religious Extremism Across Diverse Nations - Cao, Lansheng (Journal of religion and health, 2025)
Geopolitical risk has become a major driver of instability, intensifying tensions that often escalate into religious violence worldwide. The complex relationship between geopolitical disruptions and the escalation of religious conflicts demands urgent attention to better understand its broader implications for global peace and security. This investigation examines the asymmetric impact of geopolitical risk on religious violence across ten selected countries: USA, Nigeria, India, Indonesia, Egypt, Myanmar, Sri Lanka, Israel, France, and Brazil. Unlike earlier studies, which mainly employed panel data tools and often neglected the unique economic environments of individual nations, the present work utilizes the advanced quantile-on-quantile tool. This approach allows for the independent assessment of variable changes within each nation, improving precision and offering a more profound comprehension of each country’s unique attributes. The findings highlight a strong and significant positive relationship between geopolitical risk and religious violence in most of the selected nations, with each country exhibiting unique patterns and responses to these dynamics. The results highlight the critical role of policymakers in applying rigorous estimations and forming customized policies to navigate the complex interplay between geopolitical risk and religious violence, ensuring more effective and context-specific solutions.